(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents a comparative analysis of landscape terminology in English and Uzbek, focusing on the vocabulary used to describe geographical features and their associated cultural connotations. The research extends beyond simple lexical equivalence, delving into the semantic subtleties and pragmatic implications of differing word choices in each language. Employing a mixed-methods approach that integrates dictionary analysis with corpus-based research, the study aims to uncover both the similarities and divergences in how these languages conceptualize and classify landscapes. The analysis reveals not only variations in specific vocabulary but also highlights the broader cultural perspectives and environmental understandings embedded within the linguistic structures of English and Uzbek. This comparative framework illuminates potential challenges and opportunities for accurate translation and effective cross-cultural communication, particularly within the domains of environmental discourse and literary translation. The findings contribute to a deeper understanding of the intricate relationship between language, culture, and the environment, offering insights into how different linguistic systems reflect and shape our perception of the natural world. The study further suggests avenues for future research into the impact of linguistic differences on cross-cultural environmental awareness and the preservation of cultural nuances in translation.